Art and its institutions : current conflicts, critique and collaborations - Möntmann, Nina (London : Black Dog Publishing, 2006)
- The utopian institution? / Cecilia Gelin##- Art and its institutions / Nina Montmann##- The changing normative foundations of Nordic welfare state institutions / Nanna Kildal##- Curating with institutional visions / a roundtable talk with: Roger M. Buergel, Anselm Franke, Maria Linda, Nina Montmann##- Spaces of conflict / Mike Bode and Staffan Schmidt##- "A museum is not a business, It is run in a businesslike fashion" / Andrea Fraser##- Opacity: current considerations on art institutions and the economy of desire / Nina Montmann##- Institutional desires / Sven-Olov Wallenstein##- Game within the game: institution, institutionalisation and art education / Beatrice Von Bismarck##- This is not an exhibition. On the practical ties and symbolic differences between the agency of the art institution and the work of those on its outside / Jan Verwoert##- The trouble with institutions, or, art and its publics / Simon Sheikh##- Friends of the divided mind / an email conversation between Marita Muukkonen and Chris Evans##- There is no alternative: the future is self-organised. Part 1. / Anthony Davies, Stephan Dillemuth, Jakob Jakobsen##- Collective interest / 16 Beaver group in conversation with Tone Hansen and Trude Iversen.
CCS Gent
CCS Gent
boek